Swine gut microbiome associated with non-digestible carbohydrate utilization - Pandey, Sriniwas; Kim, Eun Sol; Cho, Jin Ho; Song, Minho; Doo, Hyunok; Kim, Sheena; Keum, Gi Beom; Kwak, Jinok; Ryu, Sumin; Choi, Yejin; Kang, Juyoun; Lee, Jeong Jae; et al. (Frontiers in Veterinary Science, 2023)
Non-digestible carbohydrates are an unavoidable component in a pig's diet, as all plant-based feeds contain different kinds of non-digestible carbohydrates. The major types of nondigestible carbohydrates include non-starch polysaccharides (such as cellulose, pectin, and hemicellulose), resistant starch, and non-digestible oligosaccharides (such as fructooligosaccharide and xylo-oligosaccharide). Non-digestible carbohydrates play a significant role in balancing the gut microbial ecology and overall health of the swine by promoting the production of short chain fatty acids. Although non-digestible carbohydrates are rich in energy, swine cannot extract this energy on their own due to the absence of enzymes required for their degradation. Instead, they rely on gut microbes to utilize these carbohydrates for energy production.Despite the importance of non-digestible carbohydrate degradation, limited studies have been conducted on the swine gut microbes involved in this process. While next-generation highthroughput sequencing has aided in understanding the microbial compositions of the swine gut, specific information regarding the bacteria involved in non-digestible carbohydrate degradation remains limited. Therefore, it is crucial to investigate and comprehend the bacteria responsible for the breakdown of non-digestible carbohydrates in the gut.In this mini review, we have discussed the major bacteria involved in the fermentation of different types of non-digestible carbohydrates in the large intestine of swine, shedding light on their potential roles and contributions to swine nutrition and health.